Notoginsenoside R1 attenuates high glucose-induced endothelial damage in rat retinal capillary endothelial cells by modulating the intracellular redox state - Fan, Chunlan (Drug Des Devel Ther, 2017)
The aim of this study was to examine whether Notoginsenoside R1 (NR1) attenuates high glucose-induced cell damage in rat retinal capillary endothelial cells (RCECs) and to explore the mechanisms involved. The exposure of rat RCECs to high concentration of glucose (30 mM) for 72 h led to significant cytotoxicity, including decreased cell viability, reduced mitochondrial DNA copy number, increased lactate dehydrogenase release and elevated apoptosis. NR1, when present in the culture medium, markedly attenuated the high glucose-induced cytotoxicity in rat RCECs. Moreover, high glucose also induced a significant increase in intracellular reactive oxygen species and subsequently increased the activity of NADPH oxidase and poly-ADP (ribose) polymerase, whereas the activity of catalase decreased. The addition of NR1 to the medium significantly reduced the generation of reactive oxygen species, inhibited NADPH oxidase and poly-ADP (ribose) polymerase activities and increased catalase activity in RCECs, accompanied by a reduced cellular nitrotyrosine level. To explore the underlying mechanisms involved, the cellular redox status was monitored. Both the cellular NAD(+) and NADPH levels decreased significantly in high glucose medium, which resulted in a marked decrease in the NAD(+)/NADH and NADPH/NADP(+) ratios. High glucose stimulation also enhanced the accumulation of GSSG, maintaining the GSH/GSSG ratio lower than that in the control group with 5.5 mM glucose. When treated with NR1, the cellular NAD(+), NADPH and GSH concentrations increased, and the ratios of NAD(+)/NADH, NADPH/NADP(+) and GSH/GSSG increased, similar to the control group. These results demonstrate that NR1 attenuates high glucose-induced cell damage in RCECs. Therefore, NR1 may exert its protective effects via mechanisms that involve changes in the cellular redox state.